2010
DOI: 10.1523/jneurosci.4000-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cholesterol on Catecholamine Release from the Fusion Pore of Large Dense Core Chromaffin Granules

Abstract: Changes in cellular cholesterol can affect exocytosis, but the influence of cholesterol in fusion pore kinetics is unclear. Using carbon fiber amperometry, we monitored quantal catecholamine release from rat chromaffin cells. To bypass any possible effect of cholesterol perturbation on ion channels or the colocalization of voltage-gated Ca 2ϩ channels with sites of exocytosis, exocytosis was stimulated via uniform elevation of cytosolic [Ca 2ϩ ] (with whole-cell dialysis of a Ca 2ϩ -buffered solution). Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 45 publications
6
53
0
Order By: Relevance
“…Further, the presence of molecules that oppose membrane rupture, such as, e.g., cholesterol, enhance survival of the nucleated hemifusion diaphragm and thereby facilitate expansion of the HD toward a more metastable size. Because the subsequent rupture of such an HD involves rim-pore formation, the presence of cholesterol is thus expected to enhance the propensity of pore-flickering (28). Finally, fluctuations in tension will discern between closure or complete opening of the rim-pore.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the presence of molecules that oppose membrane rupture, such as, e.g., cholesterol, enhance survival of the nucleated hemifusion diaphragm and thereby facilitate expansion of the HD toward a more metastable size. Because the subsequent rupture of such an HD involves rim-pore formation, the presence of cholesterol is thus expected to enhance the propensity of pore-flickering (28). Finally, fluctuations in tension will discern between closure or complete opening of the rim-pore.…”
Section: Discussionmentioning
confidence: 99%
“…The local lipid environment is strongly involved in regulating fusion pore formation, stability and the successful completion of exocytosis (Chasserot-Golaz et al, 2010). Membrane cholesterol has been shown to have an effect on chromaffin granule morphology (Tsuchiya et al, 2010), fusion pore kinetics and number of exocytotic events (Wang et al, 2010). Moreover, it has been shown that elevated cholesterol in b-cells causes reduced Ca 2+ entry (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol’s direct effects on the dynamics of forming fusion pores has been measured in cells using amperometery (Ge et al, 2010; Wang et al, 2010; Koseoglu et al, 2011; Gruba et al, 2015; Finkenstaedt-Quinn et al, 2016). Recapituating these effects observed in cells, reconstitution of SNARE-mediated fusion in different biochemical settings also shows more efficient fusion when the cholesterol content is increased in the membrane (Tong et al, 2009; Kreutzberger et al, 2015; Stratton et al, 2016).…”
Section: Effect Of Cholesterol On Snare-mediated Intracellular Membramentioning
confidence: 99%